Determinants and Effects of Subjectivity in Incentives - Gibbs, Michael; Merchant, Kenneth A.; Stede, Wim A. Van der; Vargus, Mark E. (The Accounting Review, 2004)
This study examines two questions: When do firms make greater use of subjectivity in awarding bonuses? What are the effects of subjectivity on employee pay satisfaction and firm performance? We examine these questions using data from a sample of 526 department managers in 250 car dealerships. First, the findings suggest that subjective bonuses are used to complement perceived weaknesses in quantitative performance measures and to provide employees insurance against downside risk in their pay. Specifically, use of subjective bonuses is positively related to: (1) the extent of long-term investments in intangibles; (2) the extent of organizational interdependencies; (3) the extent to which the achievability of the formula bonus target is both difficult and leads to significant consequences if not met; and (4) the presence of an operating loss. Second, we find that the effects of subjective bonuses on pay satisfaction, productivity, and profitability are larger the greater the manager's tenure, consistent with the idea that subjectivity improves incentive contracting when there is greater trust between the subordinate and supervisor